THE CAUCASIAN CENTRE OF FORMATION OF WILD DI- AND TETRAPLOID WHEATS: THE ARMENIA 2013 EXPEDITION - N. P. Goncharov; A. Sh. Melikyan; M. G. Harutyunyan; M. Ts. Hovhannisyan; L. V. Hovhannisyan; R. R. Sadoyan; O. A. Lyapunova (Вавиловский журнал генетики и селекции)
The results of an international expedition to the Republic of Armenia in the summer of 2013 are presented. An important result of field work is the discovery of several habitats of wheats Triticum araraticum Jakubz. and T. boeoticum Boiss.